Permata Sinar Enterprise / Zufuan Effendi Zubir... [et al.] - Zubir, Zufuan Effendy; Abd Karim, Mohd Faizal; Yahya, Mohamad Sayuthi; Sukri, Mohd Sayuki; Ismail,, Mohd sazeri (2002)
Permata Sinar Enterprise is running optical store. This company will provide Licensed Optician with an experience, providing state of the art frame and lens technology with superior quality service. They are choosing Baling, Kedah as a business location for their company.